EFFECT OF MARKETING MIX OF CONSUMER PURCHASE DECISION TO BUY HONDA MOTORCYCLE AT THE END OF IVORY NES CV MINA WEST PASAMAN - Niswah, Khoirun - (Pendidikan Ekonomi, 2014)
This study aims to analyze: 1) the impact of products on consumer purchase decisions in buying Honda motorcycle in CV MINA NES Edge Ivory West Pasaman, 2) The effect of price on consumer purchasing decisions in buying Honda motorcycle in CV MINA NES Edge Ivory West Pasaman 3) the effect of promotions on consumer purchasing decisions in buying honda motorcycle in CV MINA NES Edge Ivory West Pasaman, 4) Effect of distribution on consumer purchasing decisions in buying honda motorcycle in CV MINA NES Edge Ivory West Pasaman, 5) impact of products, price , promotion and distribution together on consumer purchasing decisions in buying honda motorcycle in CV MINA NES Edge Ivory West Pasaman. This type of research used in this study is a descriptive study associative. The population of this study is that consumers who buy a motorcycle honda, its population is unknown. The sampling technique used purposive sampling with a sample size of 80 people. Data analysis techniques: descriptive analysis and inductive analysis. The results showed that: 1) There is a significant relationship between the variables of products on consumer purchasing decisions in buying Honda motorcycle in CV MINA NES Edge Ivory West Pasaman. Seen from tcount (2:42)> t table (1.99) This is evidenced by the coefficient value of 0093 means that if the product is increased by 1%, the purchasing decision is also increased by 1%. 2) There is a significant relationship between variable prices on consumer purchasing decisions in buying Honda motorcycle in CV MINA NES Edge Ivory West Pasaman. Seen from tcount (6:35)> t table (1.99), this is evidenced by the coefficient value of 0:49 means that if the price increases by 1%, the purchasing decision is also increased by 1%. 3) There is a significant relationship between the variables promotion on consumer purchasing decisions in buying Honda motorcycle in CV MINA NES Edge Ivory West Pasaman. Seen from tcount (3:28)> t table (1.99), this is evidenced by the coefficient value of 0:26 means that if the promotion increased by 1%, the purchasing decision is also increased by 1%. 4) There is a significant relationship between the variable distribution of consumer purchasing decisions in buying Honda motorcycle in CV MINA NES Edge Ivory West Pasaman. Seen from tcount (2:41)> t table (1.99), this is evidenced by the coefficient value of 0.31 means that if the distribution is increased by 1%, the purchasing decision is also increased by 1%. 5) Variable product, price, promotion and distribution of jointly have a positive influence on consumer purchasing decisions in buying Honda motorcycle in CV MINA NES Edge Ivory West Pasaman with the value of F (52.04)> F table (2:47) and sig (0000) <Alpha (0005).